Usability and Clinical effectiveness of the NEVERMIND system - Petros, Nuhamin Gebrewold (Karolinska Institutet, 2023)
The data provided is from the NEVERMIND trial, a randomized controlled trial to assess the effectiveness of the NEVERMIND system in reducing depressive symptoms among individuals with severe somatic conditions. The dataset includes data on 255 patients diagnosed with breast cancer or prostate cancer who were randomly assigned to the NEVERMIND intervention or a control group. The data includes baseline sociodemographic data, structured questionnaires on mental health symptoms (Beck Depression Inventory-II and Depression, Anxiety and Stress Scale-21), acceptability and usability (System Usability Scale, user version of the Mobile Application Rating Scale, Perceived usefulness and Perceived ease of use) and recorded log data collected at 12 weeks to assess the effectiveness, usability, and acceptability of the NEVERMIND system.

The NEVERMIND system consists of a shirt and a smart phone. Sensors in the shirt and an application in the smart phone data collect data on the patient's condition.

The main purpose of the dataset is to investigate the relationship between the clinical effectiveness, usability, and acceptability of the NEVERMIND eHealth intervention for treating depressive and stress symptoms in breast and prostate cancer patients. Linear mixed model analyses and multiple regression were used to evaluate the association between clinical effectiveness, usability, and acceptability variables.

The dataset is relevant for reuse by researchers interested in investigating the effectiveness of eHealth interventions for treating depressive and stress symptoms in cancer patients.

The dataset consists of a file called dataset_usability_clinical_nevermind.xlsx, which contains a table with data collected from individuals in the study. A codebook file (Codebook.xlsx) is also included and defines the variables used in the table.

Den tillhandahållna datan kommer från NEVERMIND-testet, en randomiserad kontrollerad studie för att utvärdera effektiviteten av NEVERMIND-systemet för att minska depressiva symtom hos personer med svåra somatiska tillstånd. Datasetet inkluderar data från 255 patienter som diagnostiserats med bröstcancer eller prostatacancer som slumpades till antingen NEVERMIND-interventionen eller en kontrollgrupp. Datasetet inkluderar sociodemografisk data vid baseline, strukturerade enkäter om psykisk hälsa (Beck Depression Inventory-II och Depression, Anxiety and Stress Scale-21), acceptabilitet och användbarhet (System Usability Scale, användarversionen av Mobile Application Rating Scale, upplevd nytta och upplevd användarvänlighet) och registrerade loggdata insamlade vid 12 veckors uppföljning för att bedöma effektiviteten, användbarheten och acceptabiliteten för NEVERMIND-systemet.

NEVERMIND-systemet består av både en tröja och en mobiltelefon utrustade med ”smartphoneteknologi”. Med hjälp av sensorer i tröjan och en applikation på mobiltelefonen samlas data in om patienternas tillstånd.

Huvudsyftet med datasetet är att undersöka sambandet mellan den kliniska effektiviteten, användbarheten och acceptabiliteten av NEVERMIND eHälsoingripandet för att behandla depressiva och stressymtom hos bröst- och prostatacancerpatienter. Linjär blandad modellanalys och multipel regression användes för att utvärdera sambandet mellan klinisk effektivitet, användbarhet och acceptabilitetsvariabler.

Datasetet är relevant för återanvändning av forskare som är intresserade av att undersöka effektiviteten av eHälsoingripanden för att behandla depressiva och stressymtom hos cancerpatienter.

Datasetet består av en fil (dataset_usability_clinical_nevermind.xlsx) som innehåller en tabell med data samlade från deltagarna i studien samt en fil (Codebook.xlsx) som innehåller en lista över variablerna med förklarande text.
Användarvänlighet och klinisk effektivitet i systemet NEVERMIND
Keywords: Mental Health; Psykisk hälsa; eHealth; ehälsa; depression; depression; stress; stress; Medical and Health Sciences; Medicin och hälsovetenskap; Cancer and Oncology; Cancer och onkologi; Applied Psychology; Tillämpad psykologi; Information Systems, Social aspects; Systemvetenskap, informationssystem och informatik med samhällsvetenskaplig inriktning; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin; Epidemiology; Epidemiologi